Adjustment of the Yellow River Water Allocation Scheme Based on Unused Water Permits - DAI Xiaoping; ZHANG Xiaohong; WAN Fubing (Renmin Zhujiang)
Adjustment of the Yellow River Water Allocation Scheme (“Scheme 1987”) is vital for the water resource management of the Yellow River Basin and is a good example to explore the method of river water allocation adjustment.Most researchers analyzed government adjustment methods while market adjustment methods were not fully discussed.This paper put forward a new water allocation scheme based on unused water permits.In the new scheme,assignable water resources will be calculated by subtracting ecological water needs from changed river runoff.Unused water permits will be canceled and returned to the Yellow River Basin Commission and the canceled water permits will be sold to different provinces by auction.The water allocation ratio of provinces will be calculated by the sum of left permits and bought permits.The canceled water permits of Shaanxi Province,Shanxi Province,Henan Province,and Hebei Province and Tianjin City were calculated to be 662,1 417,154,1 362 million m3 respectively.Cancellation of water permits will have a greater impact on Shanxi Province than other provinces.The loss of these provinces should be compensated with the investment of the central government and the fund of water permit auction.This new water scheme adjustment method can provide a novel idea for river water allocation adjustment.